IMPLEMENTASI FOOD ESTATE TERHADAP TINGKAT PARTISIPASI ANGKATAN KERJA DI INDONESIA - Devi andriyani; Indrayani Indrayani; cut putri mellitasari; Fanny Nailufar (Universitas Teuku Umar, 2022)
Food estate policies implemented by the government in several provinces are aimed at improving the welfare of farmers and increasing the production of agricultural products. an increase in farmers' welfare is indicated by an increase in the farmer's exchange rate (NTP) and an increase in the production of agricultural products as indicated by the growth of GRDP in the agricultural sector. This study aims to determine how much influence the implementation of food estate has on employment in the agricultural sector (TPAK). This study was analyzed by panel data regression and the selected model is the Fixed Effect Model. The results showed that the GRDP growth variable in the agricultural sector had a positive and significant effect on TPAK. Meanwhile, the NTP variable has a negative and insignificant effect on TPAK in the provinces where the food estate policy is applied